Self Regulated Learning: Its Role and Influence in Increasing Student Achievement and Interest in Learning - Amina Intes; Embrechts Xavier; Mahon Nitin (Yayasan Adra Karima Hubbi, 2024)
Background. Nowadays, many students carry out learning activities without any planning and evaluation of their learning itself. So many students do assignments haphazardly, submit assignments not on time and are late in learning. This is because students are not yet able to regulate themselves in learning which can influence students' low academic achievement. Purpose. The aim of this research isto improve student achievement and interest in learning through self-regulated learning. Method. Method used The researcher used a quantitative method in conducting this research by distributing research questionnaires via Google Form.Results of this researchThere have been many important findings that self-regulated learning can help students improve their ability to learn and understand material. Results. Limitations of this researchis that researchers only conduct surveys on certain students so it will be difficult to obtain appropriate data in choosing ideal student learning methods.Researchers hopefor future researchers to be able to conduct surveys on all students and not just certain students. Conclusion. Conclusions from this researchexplained that self-regulated learning plays an important role in increasing student achievement and interest in learning. Because it can make it easier for students to understand the lessons explained by the teacher.